2010
DOI: 10.1249/mss.0b013e3181c67d82
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Paralympic Athletes in Selected Sports

Abstract: Athletes regulated their average work intensity during the field tests in the five Paralympic sports to approximate their individualized VT measured during incremental arm cranking exercise test, and this intensity was within the range recommended by the American College of Sports Medicine to improve cardiorespiratory fitness in well-trained subjects. In addition, performance of Paralympic athletes in these sports was highly dependent upon athletes' aerobic fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 24 publications
8
97
1
9
Order By: Relevance
“…VO 2peak -values as a result of incremental maximal cardiopulmonary arm-cranking, present a close relationship with VO 2 measured during a 5 km simulated race (Bernardi et al 2010). …”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…VO 2peak -values as a result of incremental maximal cardiopulmonary arm-cranking, present a close relationship with VO 2 measured during a 5 km simulated race (Bernardi et al 2010). …”
Section: Introductionsupporting
confidence: 53%
“…Forbes et al (2010) reported no differences in VO 2 , but higher values in all other variables in simulated compared to natural conditions. Other studies have used simulated conditions to describe sitskiers' physical fitness and consequently give advice on training and performance (Bernardi et al 2010(Bernardi et al , 2012Bernardi and Schena 2011). An arm cranking ergometer was used to assess both aerobic and anaerobic responses showing high values for VO 2peak , heart rate, and blood lactate (Bernardi et al 2010;Bernardi and Schena 2011), while upper body muscular strength was identified as a key factor for both aerobic and anaerobic capacity (Bernardi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the present study are therefore consistent with those, which have been reported in other WT studies of between 65 and 75% of maximum HR on hard courts. [1][2][3][4][5]12 This study is the first to take samples of HR on clay courts; hence, we cannot compare our values with other studies on the same surface. The playing surface has an implication for physiological player responses; in fact, conventional tennis studies show differences in HR between clay courts and hard court.…”
Section: Physiological and Perceptual Demandsmentioning
confidence: 99%
“…[1][2][3][4][5] Most of the studies related to the physiological demands of WT conclude that it is a healthy sport. 1, 2,5 WT players have 20 s to rest between points and 90 s between changes of side, 6 the same rule as in conventional tennis. The total time (TT) of a singles WT match is between 50 and 80 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation